PRIGo: a new multi‐axis goniometer for macromolecular crystallography. (8th May 2015) - Waltersperger, Sandro; Olieric, Vincent; Pradervand, Claude; Glettig, Wayne; Salathe, Marco; Fuchs, Martin R.; Curtin, Adrian; Wang, Xiaoqiang; Ebner, Simon; Panepucci, Ezequiel; Weinert, Tobias; Schulze‐Briese, Clemens; et al.
<x xml:space="preserve">Abstract</x> The Parallel Robotics Inspired Goniometer (PRIGo) is a novel compact and high‐precision goniometer providing an alternative to (mini‐)kappa, traditional three‐circle goniometers and Eulerian cradles used for sample reorientation in macromolecular crystallography. Based on a combination of serial and parallel kinematics, PRIGo emulates an arc. It is mounted on an air‐bearing stage for rotation around ω and consists of four linear positioners working synchronously to achieve x, y, z translations and χ rotation (0–90°), followed by a ϕ stage (0–360°) for rotation around the sample holder axis. Owing to the use of piezo linear positioners and active correction, PRIGo features spheres of confusion of <1 µm, <7 µm and <10 µm for ω, χ and ϕ, respectively, and is therefore very well suited for micro‐crystallography. PRIGo enables optimal strategies for both native and experimental phasing crystallographic data collection. Herein, PRIGo hardware and software, its calibration, as well as applications in macromolecular crystallography are described.